2017
DOI: 10.4238/gmr16019538
|View full text |Cite
|
Sign up to set email alerts
|

Regularized quantile regression applied to genome-enabled prediction of quantitative traits

Abstract: ABSTRACT. Genomic selection (GS) is a variant of marker-assisted selection, in which genetic markers covering the whole genome predict individual genetic merits for breeding. GS increases the accuracy of breeding values (BV) prediction. Although a variety of statistical models have been proposed to estimate BV in GS, few methodologies have examined statistical challenges based on non-normal phenotypic distributions, e.g., skewed distributions. Traditional GS models estimate changes in the phenotype distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
(26 reference statements)
0
8
0
2
Order By: Relevance
“…The ability to choose the "best" relationship between the phenotype and markers increases the predictive performance of the model. According to the authors of [11] and [12], when the conditional distributions of Y are non-normal (for instance, skewed), the mean might not be the best way to describe the functional relationship between the variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to choose the "best" relationship between the phenotype and markers increases the predictive performance of the model. According to the authors of [11] and [12], when the conditional distributions of Y are non-normal (for instance, skewed), the mean might not be the best way to describe the functional relationship between the variables.…”
Section: Discussionmentioning
confidence: 99%
“…This feature allows QR to examine all of the conditional distributions, in order to investigate skewness and heteroscedasticity. From a GS viewpoint, we can choose the "best" conditional quantile to represent the relationship between the dependent and independent variables, thus increasing the accuracy of the genomic estimated breeding value (GEBV) prediction of individual genetic merits [12]. However, because of the high dimensionality commonly found in GS studies, a variation of QR, denoted by regularized quantile regression (RQR) [13] should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…To deal with dimensionality problems in GWS studies, which are common in the marker matrix, Li and Zhu [26] proposed the Regularized Quantile Regression (RQR). The use of RQR in a GWS study was proposed by Nascimento et al [27], in order to estimate GEBV for different quantiles of the phenotype of interest [28,29]. In their study, Nascimento et al [27] used RQR to estimate GEBV from simulated data with scenarios with different skewness levels in the phenotype distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The use of RQR in a GWS study was proposed by Nascimento et al [27], in order to estimate GEBV for different quantiles of the phenotype of interest [28,29]. In their study, Nascimento et al [27] used RQR to estimate GEBV from simulated data with scenarios with different skewness levels in the phenotype distribution. The results of the RQR were compared to those of the BLASSO (Bayesian Least Absolute Shrinkage and Selection Operator) method, and the authors observed a lower mean square error of the former.…”
Section: Introductionmentioning
confidence: 99%
“… Varona et al (2008) proposed using linear mixed models with asymmetric distributions in the residuals to tackle the problem in the context of animal breeding when pedigree information is available. Nascimento et al (2017) proposed the Regularized Quantile Regression as a way to overcome the issue of non-symmetric distributions when marker information is available.…”
mentioning
confidence: 99%